Factor VIII inhibitor development in Egyptian hemophilia patients: does intron 22 inversion mutation play a role? - Laila M. Sherief; Osama A. Gaber; Hala Mosaad Youssef; Hanan S. Sherbiny; Wesam a Mokhtar; Asmaa A. A. Ali; Naglaa M. Kamal; Yehia H. Abdel Maksoud (BMC, 2020)
Abstract Background Hemophilia A (HA) is an X-linked recessive bleeding disorder characterized by qualitative and quantitative deficiency of factor VIII (FVIII). The development of inhibitor antibodies against FVIII is the most challenging complication of treatment. Mutations in the FVIII gene is one of the genetic factors that leads to development of FVIII inhibitors especially intron 22 inversion (Inv22). Objectives This study was carried out to assess the frequency of Inv22 of FVIII gene in Egyptian patients with hemophilia A and its role as a risk factor for developing inhibitors. Patients and methods Seventy-two patients with severe HA and 48 patients with moderate HA were enrolled in the current study. All patients were treated on demand with either plasma-derived factor VIII or recombinant factor VIII concentrates. Genotyping of FVIII Inv22 was performed by LD-PCR while the presence and magnitude of inhibitor activity in blood was determined by the Bethesda assay. Results Around 23% of all hemophilia cases had positive Inv22. Intron 22 inversion mutation was detected in 6 and 33% of patients with moderate and severe HA respectively. Twenty-one cases (18%) of all hemophilic patients developed inhibitors. Thirty-7% of patients with Inv22 had inhibitor in their blood, almost all, but one, had severe HA. The risk of an inhibitor development during replacement therapy was four folds higher among Inv22 positive cases as compared with mutation negative peers (OR 4.3, 95% CI 1.6-11.9, P = 0.003). Conclusions The prevalence of Inv22 of F VIII in Egyptian hemophiliacs is nearly like that of other population. This mutation was more frequently detected among severe hemophilic patients as compared with moderately affected peers. The presence of Inv22 mutation significantly predispose to FVIII inhibitor development.